PENGEMBANGAN DESA WISATA DI KABUPATEN ENDE SEBAGAI UPAYA PENCEGAHAN URBANISASI - H. N. Mari, Natalia Adel (Universitas Nusa Cendana, 2022)
The change from mass tourism to alternative tourism provides an advantage for tourist villages to be an option in tourism development. Rural areas with their unique characteristics, such as unspoiled natural environment, beautiful natural scenery, various kinds of animals and plants, rural people and culture, present a unique experience to tourists. This study uses a qualitative method with a descriptive-analytic model. Tourism villages are able to reduce the urbanization of people from villages to cities because many economic activities in villages can be created. In addition, tourist villages can be an effort to preserve and empower the potential of local culture and local wisdom values ​​that exist in the community. As an effort to suppress the existing rate of urbanization, the development of tourist villages is a form of solution that can be carried out by every village. In developing a village into a tourist village, many aspects are absorbed, especially the provision of jobs in the village which are increasingly varied and able to absorb the existing workforce in rural areas.